Strategic Alliances, Competitive Advantages, And Bandwagon Effect In The Perum Perhutani Wood Industry - Taufik Setyadi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
The establishment of Strategic Alliances or operational cooperation with strategic partners of the Wood Industry around the Perum Perhutani work area is a necessity to increase competitiveness. This study attempts to elaborate on the Strategic Alliance between the Perhutani Wood Industry and its partners to be able to achieve a Competitive Advantage through the development of Market Areas and the development of Product Innovations or in other words to find out to what extent the Strategic Alliance can improve the position of the Perum Perhutani Wood Industry Competitive Advantage. In addition, this study also aims to determine the extent to which the implementation of the Strategic Alliance, through the development of Market Areas and Product Innovation in the Perum Perhutani Wood Industry, influences increasing Competitive Advantage. This research is descriptive and uses a qualitative approach. This research uses a literature study technique and utilizes data sources obtained from several locations, namely (1) Perhutani Forestry Institute Library, (2) Brawijaya University Central Library, and (3) Discussion with colleagues. From the research results, it is known that the Strategic Alliance model that aims to increase Competitive Advantage is the most appropriate to be applied in Perum Perhutani is a form of Strategic Alliance that focuses on the interests of cooperation in increasing Product Innovation to realize Competitive Advantage, compared to the Strategic Alliance through the development of Market Areas. It is necessary to redevelop a good Strategic Alliance with the Wood Industry business partner Perum Perhutani by implementing: (1) Reconciliation of the Wood Industry business actors who join based on compatibility, mutual need, and mutual benefit; (2) Focus and professional; (3) Pooling of resources on what is already owned by the wood industry business partners so that a perfect alliance will have an impact on the success of Perum Perhutani to become a superior company.